Woman’s Resistance as Seen in Jane Eyre and Wide Sargasso Sea - Anna Anganita Theresia Latumeten (Faculty of Letters Universitas Balikpapan, 2021)
This paper focuses on the depictions of the mad woman figure in two novels, Jane Eyre by Charlotte Brontë and Wide Sargasso Sea by Jean Rhys. Using comparative literature, both texts are seen in the light of woman’s resistance as depicted by the characters “Bertha Mason” and “Antoinette Cosway” from Jane Eyre and Wide Sargasso Sea, respectively. The novels used in this descriptive study are the primary texts. The findings show how Wide Sargasso Sea shows woman’s resistance when being compared to Jane Eyre, giving the mad woman character a voice on her own and showing an attempt to free herself from the forms of domination she experiences.